Carte du Golphe de St. Laurent et pays voisins pour servir à l'Histoire générale des voyages - Bellin, Jacques Nicolas, 1703-1772 ([Paris], 1757)
Hand coloured. Prime meridian Paris. Decorative title cartouche. Bar scale in French common leagues. CNS map no. 5. -- Plate nos. lower left and right: Tom XIII in 4°. No. 2; Tome 14 in 8°. Page 263.